1999
DOI: 10.1094/phyto.1999.89.8.707
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Distribution and Molecular Variation of Isolates of Three Whitefly-Borne Closteroviruses of Cucurbits: Lettuce Infectious Yellows Virus, Cucurbit Yellow Stunting Disorder Virus, and Beet Pseudo-Yellows Virus

Abstract: The geographic incidence and molecular variation of three whitefly-borne closteroviruses (lettuce infectious yellows virus [LIYV], cucurbit yellow stunting disorder virus [CYSDV], and beet pseudo-yellows virus [BPYV]) were studied in cucurbits collected from several distinct geographic locations. Of 498 samples analyzed, none were found to be infected by LIYV. Sixty-nine samples collected in the Middle East and Mediterranean Europe were found infected by CYSDV, and twelve samples from Crete and Italy were infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
59
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 21 publications
9
59
0
2
Order By: Relevance
“…Analysis of CYSDV CP showed that the studied isolates had low genetic diversity in the CP and complemented previous studies [72]. Thus, CYSDV could be divided into two divergent subpopulations: a 'western' (isolates from Jordan, Lebanon, North America, Spain, France, Tunisia, Greece and Turkey) and an 'eastern' subpopulation (isolates form Saudi Arabia and Iran) [12,72,73,80,95]. Five coding and one non-coding genomic regions of a CYSDV population were examined in different cucurbit hosts in Spain [51].…”
Section: Molecular Biologysupporting
confidence: 77%
See 3 more Smart Citations
“…Analysis of CYSDV CP showed that the studied isolates had low genetic diversity in the CP and complemented previous studies [72]. Thus, CYSDV could be divided into two divergent subpopulations: a 'western' (isolates from Jordan, Lebanon, North America, Spain, France, Tunisia, Greece and Turkey) and an 'eastern' subpopulation (isolates form Saudi Arabia and Iran) [12,72,73,80,95]. Five coding and one non-coding genomic regions of a CYSDV population were examined in different cucurbit hosts in Spain [51].…”
Section: Molecular Biologysupporting
confidence: 77%
“…Early studies based on single-strand conformational polymorphism (SSCP) and sequencing of the Hsp70h and CP gene of CYSDV isolates from different geographical areas showed slightly distinct CP and Hsp70h patterns [51,72,73,80]. Hsp70h-based analysis showed that CYSDV population in the same plant was closely related but had one predominant variant independent of the host [73].…”
Section: Molecular Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…RT-PCR products, as used here, represent the mixture of virus sequence variants with the major sequence reflected as the prominent bands in the SSCP patterns (Rubio et al, 1999(Rubio et al, , 2001. To assess whether the major sequence variants of 33 CMV isolates from CMV-infected plants of Destiny III were different from those in the original inocula (CMVinfected plants of small sugar pumpkin), SSCP analysis of the XhoI-digested RT-PCR products of the CP+39NTR region (972 bp, see Fig.…”
Section: Comparison Of Major Sequences From Cmvinfected Transgenic Anmentioning
confidence: 99%